2019
DOI: 10.1038/s41467-019-12215-4
|View full text |Cite
|
Sign up to set email alerts
|

A ribose-functionalized NAD+ with unexpected high activity and selectivity for protein poly-ADP-ribosylation

Abstract: Nicotinamide adenine dinucleotide (NAD+)-dependent ADP-ribosylation plays important roles in physiology and pathophysiology. It has been challenging to study this key type of enzymatic post-translational modification in particular for protein poly-ADP-ribosylation (PARylation). Here we explore chemical and chemoenzymatic synthesis of NAD+ analogues with ribose functionalized by terminal alkyne and azido groups. Our results demonstrate that azido substitution at 3′-OH of nicotinamide riboside enables enzymatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 57 publications
0
56
0
3
Order By: Relevance
“…Additional targeting of recombinant ARH3 to the mitochondrial matrix could reverse the artificially induced PAR, demonstrating that the conditions present in mitochondria support the full life cycle of the modification [187,188]. Furthermore, permeabilization of cells and subsequent incubation with 3 -azido_NAD + allowed detecting mitochondrial-localized PAR chains by confocal microscopy [171]. However, a recent analysis using ARTD1 knockout cells revealed that the observed mitochondrial ADP-ribosylation is most likely not dependent on ARTD1 [155].…”
Section: Adp-ribosylation In Mitochondriamentioning
confidence: 99%
See 1 more Smart Citation
“…Additional targeting of recombinant ARH3 to the mitochondrial matrix could reverse the artificially induced PAR, demonstrating that the conditions present in mitochondria support the full life cycle of the modification [187,188]. Furthermore, permeabilization of cells and subsequent incubation with 3 -azido_NAD + allowed detecting mitochondrial-localized PAR chains by confocal microscopy [171]. However, a recent analysis using ARTD1 knockout cells revealed that the observed mitochondrial ADP-ribosylation is most likely not dependent on ARTD1 [155].…”
Section: Adp-ribosylation In Mitochondriamentioning
confidence: 99%
“…To further facilitate the incorporation of both modified metabolites into ADP-ribosylation, ARTs were genetically modified to favor NAD + analogues over natural NAD + [ 167 ]. In addition to these approaches that involve click-it chemistry, another study investigated in the synthesis of an NR analog that can be taken up by cells and is locally converted to 3′-azido_NAD + by the nicotinamide riboside kinase 1 and NMNAT1 [ 171 ]. The authors describe 3′-azido_NAD + to exhibit a high activity and specificity to ARTD1 and ATD2-catalyzed protein ADP-ribosylation and the resulting PAR chains to show a certain degree of resistance towards PARG-mediated degradation.…”
Section: Detection Of Mono-adp-ribosylationmentioning
confidence: 99%
“…The PARP family comprises 17 nucleoproteins with four domains of interest: a DNA-binding domain, a caspase-cleaved domain, an auto-modification domain, and a catalytic domain (43). When PARP detects DNA double stand breaks, it initiates a polymeric adenosine diphosphate ribose (polyADP-ribose or PAR) chain with NAD + as the substrate (44). The highly conserved PAR polymer reaches as long as 200 nucleotides and transfers one unit to target proteins, whereas PARP1, PARP2, PARP3, and PARP5a characteristically add repeated ADP-ribose units (45).…”
Section: Mechanism Of Parp1 Actionmentioning
confidence: 99%
“…Recently, another group has for the first time explored the modifications of nicotinamide riboside for protein PARylation studies [54]. To that end, Zhang et al reported a set of three NAD + analogs modified with either an alkyne or azide group at the 3′-position of nicotinamide riboside (Figure 3, 21 – 23 ) and their 2′-counterparts (not shown), which are accessible by either chemical or chemoenzymatic methods.…”
Section: Nad Analogs To Study Protein Adp-ribosylationmentioning
confidence: 99%